Prophylactic use of NSAIDs by athletes: A risk/benefit assessment - Warden, S. J. (The Physician and Sportsmedicine, 2010)
Athletes often seek artificial means to gain advantage and prolong participation when competing. This often involves taking naturally occurring or chemically synthesized compounds. The World Anti-Doping Agency does not prohibit the use of nonsteroidal anti-inflammatory drugs (NSAIDs) because these agents are not performance enhancing, and their analgesic and anti-inflammatory effects are at best performance enabling. Consequently, athletes have relatively unrestricted access to NSAIDs, which are readily available as over-the-counter drugs. However, concern has been raised on athletes` prophylactic use of these agents. Data from many sporting fields have consistently demonstrated that many individuals self-administer NSAIDs prior to athletic participation to prevent pain and inflammation before it occurs. However, scientific evidence for this approach is currently lacking, and athletes should be aware of the potential risks in using NSAIDs as a prophylactic agent. These agents are not benign, and can produce significant side effects, including gastrointestinal and cardiovascular conditions, as well as musculoskeletal and renal side effects. The latter side effects appear paradoxical to the rationale for prophylactic use of NSAIDs. This article discusses current observations regarding athlete use of NSAIDs, and the possible benefits and potential risks of their use.